The approach to the post-1964 dictatorship in History Teaching (1985-2015): is it possible to think about a pedagogy of memory in Brazil? (Clepsidra - Interdisciplinary Journal of Memory Studies, 2021)
The article presents a reflection on the possibilities of a “memory pedagogy” in Brazil based on the analysis of teaching experiences from the post-1964 dictatorial past in basic education reported by teachers at scientific events. We investigated the annals of three events in the area of History and History Teaching carried out between 1985 and 2015, in which we identified 45 communications on teaching from the dictatorial past of a total of 1,200 analyzed papers. The debate proposed here takes into account the relationship between teaching the history of the dictatorship and the Brazilian transition to democracy between 1974 and 1988.
Keywords: history teaching, post-1964 civil-military dictatorship, memory, democratic transition